Pengaruh Indeks Pembangunan Manusia (IPM), Pertumbuhan Penduduk Dan Tingkat Pengangguran Terbuka Terhadap Tingkat Kemiskinan di Provinsi Jambi - Suherman Suherman; Rika Neldawaty; Rian Dani; Ami Markah (Universitas Batanghari, 2022)
This study aims to examine and analyze the effect of the human development index, population growth and the open unemployment rate on the poverty rate in Jambi Province. The type of data used in this study is quantitative data, while the source of data used in this study is secondary data from BPS Jambi Province. The object of this research is Jambi Province. This study uses time series data for 12 years, starting from 2010 to 2021. The analytical method used is multiple linear regression. The estimation results show that simultaneously the independent variables, namely the human development index, population growth and the open unemployment rate have a significant influence on the poverty level with a Prob value (F-statistic) of 0.00001. Partially, the independent variable human development index has a positive and significant effect on the poverty level in Jambi Province with a T value of 2.371967 and a probability value of 0.0451 or less than Î²0 = 0.05 (0.0451 < 0.05) and population growth has a positive and significant effect on the poverty rate in Jambi Province with a T count value of 2.235197 with a probability of 0.0558 or greater than Î²0 = 0.05 (0.0558 < 0.05), while the open unemployment rate has a negative and significant effect on the poverty rate in Jambi Province, the T count value is -1.541635 with a probability of 0.0356 or less than Î²0 = 0.05 (0.0356< 0.05).